Analisis Yuridis Batik Pekalongan Sebagai Produk Indikasi Geografis - Dinda Prostina Nukfikhasari; Budi Santoso (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractRegistration of batik products into Geographical Indications (GI) is very important to prevent acts of abuse by other parties and guarantee protection from the use of GI that misleads the public as the geographical origin of an item. This study aims to determine and analyzes the potential of Batik Pekalongan to obtain Geographical Indication rights and the mechanism for registering batik as a geographical indication. The research approach used is normative juridical, with descriptive analytical research specifications. Data collection techniques in the form of literature study and documentation study. The data that has been collected was analyzed descriptively and normatively qualitatively. The results of this study are that Pekalongan batik has potential as a geographical indication (GI) product because it has fulfilled several elements inherent in geographical indication products including natural, human factors or a combination of both. Registration of Geographical Indications is carried out through an application as stipulated in Article 4 of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 12 of 2019 that the application for geographical indication rights is carried out electronically or non-electronically.Keywords: potential; product; batik; geographical indicationAbstrakPendaftaran produk batik ke dalam Indikasi Geografis (IG) sangat penting untuk mencegah tindakan penyalahgunaan oleh pihak lain dan menjamin perlindungan dari penggunaan IG yang menyesatkan publik sebagai asal geografis suatu barang. Penelitian ini bertujuan untuk mengetahui dan menganalisis potensi Batik Pekalongan untuk memperoleh hak Indikasi Geografis dan mekanisme pendaftaran batik sebagai indikasi geografis. Pendekatan penelitian yang digunakan adalah yuridis normatif, dengan spesifikasi penelitian deskriptif analitis. Data yang telah terkumpul dianalisis secara deskriptif kualitatif secara normatif. Hasil penelitian ini yaitu batik Pekalongan memiliki potensi sebagai produk indikasi geografis (IG) karena sudah memenuhi beberapa unsur yang melekat pada produk indikasi geografis diantaranya yaitu faktor alam, manusia atau kombinasi keduanya. Pendaftaran Indikasi Geografis dilakukan melalui permohonan sebagaimana diatur dalam Pasal 4 Peraturan Menteri Hukum Dan Hak Asasi Manusia Republik Indonesia Nomor 12 Tahun 2019 bahwa permohonan hak indikasi geografis dilakukan secara elektronik atau non elektronik.Kata kunci: potensi; produk; batik; indikasi geografis